Why Do Children Bite Each Other? Observations in A Brazilian Nursery School - Piazzaroli, Renata F.C.; Jr, Geraldo A. Fiamenghi- (American Journal of Social Sciences and Humanities, 2018)
This study was built from observations conducted in a nursery school in a Brazilian southwest country town, based in Psychoanalysis theory. It aimed to observe the meaning of aggression, especially biting, in child’s development, under environmental influences. Child may be aggressive due to many factors, associated to relations constructed around her. Biting is one of the aspects of infant aggression that must be understood as a symptom being communicated to others. The adult must listen to what the child is trying to communicate beyond the manifested symptom. In this study, children bit each other when they tried to obtain a toy, or when they felt frustrated, isolated, unassisted by the teachers, or confined in large numbers in small spaces. Those results indicate that, at least in nursery schools, teachers must assist young children and help them cope with the new environment and challenges faced by socialization.